ChemInform Abstract: Multicomponent Domino Process for the Synthesis of Some Novel Benzo[a]chromenophenazine Fused Ring Systems Using H2SO4, Phosphotungstic Acid, and [NMP] H2PO4. Issue 37 (September 2015) - Rajeswari, M.; Khanna, Garima; Chaudhary, Ankita; Khurana, Jitender M.
Abstract Use of phosphotungstic acid or [NMP] H2PO4 as catalyst in the first condensation step provides comparable results.